(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this article centrality of the usage of symbols in the novels and short stores of Hemmingway has been elaborately pointed out in the previous section. Any portion deals with the substantially key symbols which have been represented in the possible angles and in the present sense. The images that hover around the core concepts of Hemmingway’s literary works constantly inform the reader of the gains achieved by man through an enhancement of the degradation of human life through devised strategies of war and abuse.